Networks and Firm Performance: A Case Study of Vietnamese Small and Medium Enterprises - Hung D. Pham; Petrik Runst; Kilian Bizer (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2017)
Small and medium enterprises play an important role in developing and transition economies. Recently, more attention has been paid to the role of networks in improving firm performance. By using data from the DANIDA project on SME survey with more than 2,500 manufacturing firms in Vietnam, we examine the relationship between networks and firm performance, particularly focusing on small and medium businesses. Network data covers four dimensions of networking including withinsector- network, across-sector-network, informal and formal creditors, and politicians and civil servants. Multivariate panel regressions have been applied. The results suggest that firm performance is positively related to the existence and the size of networks with individuals in a different sector and networks connecting to politicians and civil servants.
Keywords: L25; L60; L29; 330; SMEs; Networks; Firm Performance; Vietnam; Panel Data